Antioxidant activity of linear and star-shaped polypeptides modified with dopamine and glutathione. (5th June 2021) - Su, Ching-Fang; Chen, Yu-Fon; Tsai, Yi-Jen; Weng, Shao-Ming; Jan, Jeng-Shiung
Graphical abstract: Highlights: The antioxidants, dopamine and glutathione, were grafted onto linear and star-shaped polypeptides. The antioxidant activities of antioxidant-grafted polypeptides were mainly ascribed to dopamine. Antioxidant-grafted polypeptides exhibited comparable antioxidant activity regardless the polypeptide arm number. Antioxidant-grafted polypeptides exhibited good hemocompatibility and biocompatibility. Abstract: The aim of this study was to investigate the effect of topology on the antioxidative activities of antioxidant-grafted polypeptides. The linear and star-shaped poly(L-glutamic acid) (PLG) polypeptides were synthesized by N -carboxyanhydrides (NCAs) ring opening polymerization (ROP) using primary amine and polyols as initiators, followed by deprotection. Graft copolypeptides (PLG-Dopa, PLG-GSH and PLG-Dopa-GSH) were obtained by EDC/NHS coupling chemistry using dopamine (Dopa) and glutathione (GSH). Successful synthesis of these polypeptides was confirmed by 1 H NMR, MALDI TOF, GPC, UV–vis and IR spectra analyses. The conformation of polypeptides was investigated by circular dichroism (CD) spectroscopy, demonstrating the grafting of Dopa and GSH onto PLG was accompanied by a conformational change from a random coil to α-helical structure. The results showed that the antioxidant activities of PLG-Dopa and PLG-Dopa-GSH were mainly ascribed to Dopa. It was found that the conjugation of Dopa resulted in the decrease in its antioxidant activity and the antioxidant-grafted polypeptides exhibited comparable antioxidant activity regardless the polypeptide arm number. The conjugation of GSH could prolong polypeptide antioxidant activity by preventing Dopa from oxidation. It was found that both PLG-Dopa and PLG-Dopa-GSH exhibited good hemocompatibility and biocompatibility.